White matter mean diffusivity correlates with myelination in tuberous sclerosis complex. Issue 7 (23rd June 2019) - Peters, Jurriaan M.; Struyven, Robbert R.; Prohl, Anna K.; Vasung, Lana; Stajduhar, Andrija; Taquet, Maxime; Bushman, John J.; Lidov, Hart; Singh, Jolene M.; Scherrer, Benoit; Madsen, Joseph R.; Prabhu, Sanjay P.; et al.
Abstract: Objective: Diffusion tensor imaging (DTI) of the white matter is a biomarker for neurological disease burden in tuberous sclerosis complex (TSC). To clarify the basis of abnormal diffusion in TSC, we correlated ex vivo high‐resolution diffusion imaging with histopathology in four tissue types: cortex, tuber, perituber, and white matter. Methods: Surgical specimens of three children with TSC were scanned in a 3T or 7T MRI with a structural image isotropic resolution of 137–300 micron, and diffusion image isotropic resolution of 270‐1, 000 micron. We stained for myelin (luxol fast blue, LFB), gliosis (glial fibrillary acidic protein, GFAP), and neurons (NeuN) and registered the digitized histopathology slides (0.686 micron resolution) to MRI for visual comparison. We then performed colocalization analysis in four tissue types in each specimen. Finally, we applied a linear mixed model (LMM) for pooled analysis across the three specimens. Results: In white matter and perituber regions, LFB optical density measures correlated with fractional anisotropy (FA) and inversely with mean diffusivity (MD). In white matter only, GFAP correlated with MD, and inversely with FA. In tubers and in the cortex, there was little variation in mean LFB and GFAP signal intensity, and no correlation with MRI metrics. Neuronal density correlated with MD. In the analysis of the combined specimens, the most robust correlation was between white matter MD and LFB metrics. Interpretation: In TSC, diffusion imaging abnormalities in microscopic tissue types correspond to specific histopathological markers. Across all specimens, white matter diffusivity correlates with myelination.